Spatial light modulator design and generation of structured electromagnetic waves using digital light processors - Yalçınkaya, F.; Koç, T.; Pala, Zeydin (Wroclaw Univ Science Technology, 2022)
Spatial light modulators (SLMs) are versatile devices used for optical studies. These instruments have a wide area of application in photonics. Additionally, SLMs have potential utility in different applications, such as biomedical applications, laser based surgery for precise cutting and as optical tweezers to separate cells in a petri container. However, the high cost of SLM devices prevents their widespread use in many areas, including industrial areas and scientific research laboratories. This paper demonstrates how to design a digital light processor (DLP) based low-cost SLM and describes how to obtain structured electromagnetic waves with the designed SLM. Therefore, this research was undertaken to design and produce a low-cost SLM device for optical applications. For this purpose, two prerequisites had to be fulfilled, the first was to use suitable components of a projection device with DLP-based digital micro-mirror device (DMD), and the second was to eliminate unnecessary SLM components from the system. Finally, holographic images reflected on the SLM screen were created by using Mathematica software program to change the amplitude and phase of the electromagnetic waves in order to obtain the structured electromagnetic waves.
Keywords: spatial light modulator; digital micro-mirror device; digital light processing; structured electromagnetic waves; orbital angular momentum; hologram; Undergraduate; Quantization; Holography; Patterns